Aspectos metodológicos de las Guías de Práctica Clínica realizadas en la Universidad de Antioquia con base en la guía metodológica del Ministerio de Salud y Protección de Colombia (2016)
ABSTRACT: In 2010 The Colombian Ministry of Health and Social Protection (MOH) started a process to develop several evidence-based clinical practice guidelines (CPG) according to the main health priorities of the country. The National Center for Research in Evidence and Technologies in Health (an Alliance between the University of Antioquia, University Javeriana and National University of Colombia) conducted 90% of the 55 GPCs funded by the MOH; of these, the University of Antioquia leaded the development of eight. This article describes the methodological steps that were followed for the preparation of these GPC, including: creating the guideline development group, defining the focus, scope and objectives, defining the clinical question, rating the quality of primary studies, and synthesis of evidence. Subsequently, we describe the process to assess the quality of the evidence with “The Grading of Recommendations Assessment, Development and Evaluation (GRADE)” system and to formulate the recommendations. We also explain the economic assessments as well as the proposal for the implementation of the GPC. We presented a synthesis of the experience of this project at the University of Antioquia presented.